We need to find 0 so what we would do is replace the x with 3 as the question is asking and solve from there.
Let me demonstrate by using an example:
x = 4
6+x= 10
6+4=10
In this example, I replaced the x with 4 which resulted in 10.
Now, let's solve!
The answer is the third option because it results 0 and I will show you why!
First, we replace the x with 3
(3+20)(3-3)
Using our knowledge of PEMDAS we would first solve what's inside the parentheses and then multiply!
3+20= 23 and 3-3=0
Now, we multiply 23*0 and we got the answer of 0 which is what the problem is asking for.
Therefore, the correct answer is the third option or (x+20)(x-3)